The effect of ethanol extract of Andaliman (Zanthoxylum acanthopodium DC.) on kidney damage in tartrazine-induced rats - Azhari, Mhd Bayu; Febriani, Husnarika; Syukriah, Syukriah (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2022)
Tartrazine is a yellow synthetic dye with aromatic and chromo groups. It is widely used in food colouring products and cosmetics, and prolonged consumption can cause kidney damage. Andaliman (Zanthoxylum acanthopodium DC.) is a North Sumatra-native spice plant which reported as antioxidant to repair kidney damage. This study was conducted to determine the effect of ethanol extract of andaliman fruit on the morphology, ureum levels, histology, and glomerular diameter of tartrazine-induced rats. This study employed a completely randomised design (CRD). The ethanol extract of andaliman fruit was dissolved in CMC-Na 1%. Twenty-five rats were divided into 5 groups: negative control (KN), positive control (tartrazine indcution/PN), and treated groups (P1, P2, and P3 induced tartazine and treated with andaliman extract at dose 150 mg/kg BW, 300 mg/kg BW, and 450 mg/kg BW, respectively). After 30 days treatment, kidney damage was observed based on colour and surface of kidneys, kidney index, ureum level, kidney damage score, and glomerular diameter. There are no significant different in the kidney index among groups (p > 0.05). Tartrazin at a dose of 15 mg/kg BW was able to induce the kidney damage as indicated by the increase ureum levels, kidney damage score, and the decrease of glomerular diameter in the negative control. The treatment of andaliman fruit ethanol extract was able to repair the tartazine-induced kidney damage as indicated by the decrease of ureum level and kidney damage score and incread the glomerular diameter.